The effects of intrahippocampal ibotenate on resistance to extinction after continuous or partial reinforcement. - Jarrard, L; Feldon, J; Rawlins, J; Sinden, J; Gray, J (1986)
Intracerebral injections of ibotenate were used to produce, in rats, extensive cell loss in the hippocampus and dentate gyrus (complete hippocampal, CH), in the CH plus subiculum (SUB + CH), or in the subiculum plus entorhinal cortex (SUB + EC). These rats and sham-operated controls were trained to run in a straight alley for food reward delivered on a continuous (CR) or partial (PR) reinforcement schedule. In controls PR training gave rise to the well-known partial reinforcement extinction effect (PREE), i.e., greater resistance to extinction than that observed in CR-trained animals. Previous work had shown that large aspiration lesions of the hippocampal formation eliminate the PREE by increasing resistance to extinction in CR-trained animals and decreasing resistance to extinction in PR-trained animals. In the present experiments the PREE survived CH lesions, which increased resistance to extinction in both CR and PR training conditions; these effects were observed in the start and run (but not goal) sections of the alley. In contrast, subicular cell loss (in both SUB + CH and SUB + EC groups) abolished the PREE (but in the goal section only) by increasing resistance to extinction in the CR condition and decreasing resistance to extinction in the PR condition. In addition, some of the effects of PR training on start and run speeds during acquisition were altered by the CH and SUB + CH lesions. These results confirm previous data showing that the hippocampal formation plays a role in mediating the behavioural effects of PR training, but require modification of the model previously proposed to account for these data.